Implementasi Pembinaan Kompetensi Profesional Guru Studi Kasus Di MTs Darunnajah Cipining Bogor - Rokimin Rokimin; Hasbu Marzuki (Edukasiana: Journal of Islamic Education, 2022)
The development of teacher professional competence is the need for assistance in the form of professional services, which are provided by school principals through supervision, quality assurance with the aim of improving the quality of learning processes and outcomes so that the planned educational goals can be achieved. The method used in qualitative descriptive research, namely research by means of interviews to answer the formulation of the problem, but not to test the hypothesis. Thus, the main data of this study can be clearly identified from the descriptive analysis. Based on the results of the study, it was stated that the Implementation of Teacher Professional Competence Development that the school in this case had run it quite well, especially the principal who directly participated in controlling educators and education in the process of activities at school. The implementation of the coaching carried out includes: first, regular coaching, which includes spiritual coaching, discipline, as well as coaching outside of school and an annual evaluation. second, the guidance carried out by the principal is to provide motivation to teachers and provide input to teachers in the learning development unit.